SISTEM KONTROL PADA KENDARAAN RODA DUA BERPENGGERAK HIBRIDA - Didi Widya Utama; Kennard Dharmmabakti; Asrul Aziz (Jurnal Ilmiah Teknik Mesin POROS, 2014)
Abstract: This hybrid motorcycle design is to combine 5.65kW gasoline engine and 48V DC 0.5kW electrical brushless motor in serial-parallel type. Master control unit use a microcontroller ATMega16 to control gasoline engine and electrical motor alternately. Speed sensor is placed on the rear wheel to detect the motorcycle’s speed. When the motorcycle’s speed reaches the top threshold at 30km/h, it driven with gasoline engine and when the motorcycle’s speed getting lower to the bottom threshold at 5km/h, it changes with electrical motor. Battery charged with plug-in system to power supply.